Implementation of the Simple Additive Weighting (SAW) method in supporting the business transformation process of PT Virama Karya (Persero) to become PT Agrinas Jaladri Nusantara (Persero) - Adi Hutomo Suryopratomo; Ravi Ahmad Salim (Priviet Social Sciences Journal, 2025)
Business transformation is a strategy adopted by companies to maintain long-term sustainability. In support of the government's program to achieve food self-sufficiency through the development of the fisheries commodity ecosystem, PT Virama Karya (Persero), which was originally engaged in the construction sector, shifted to PT Agrinas Jaladri Nusantara (Persero) through horizontal diversification into the fisheries sector. In this case, the company transformed its business while maintaining its construction sector. This shift requires a more objective and measurable decision-making process. Although the company has implemented a weighting system, its use has been limited to assessing the feasibility of alternatives, and the final decision still relies on direct appointments. To support the transformation process, several key aspects must be considered, including the selection of a Public Accounting Firm (KAP), employee training programs, determining the best employees, and employee rotation. This study used the Simple Additive Weighting (SAW) method with a quantitative method through a descriptive approach and semi-structured interviews for data collection. This method requires criteria weighting, matrix normalization, and identification of alternative rankings to determine the most appropriate choice. This study revealed that the SAW method improves a company's ability to make objective and measurable decisions. It can be concluded that the SAW method used in this study can assist the decision-making system at PT Agrinas Jaladri Nusantara (Persero) objectively and measurably and can increase the company's cost efficiency.